P148 Factors determining the length of time between onset of symptoms and physician consultation for occupational asthma. (December 2018) - Hoyle, J; Carder, M; Money, A; Seed, M; Sen, D; Agius, RM; Van-Tongeren, M
Abstract : Introduction and objectives: Occupational asthma continues to be a significant and costly problem in the UK. The earlier asthma is diagnosed and exposure removed the better the prognosis. It is therefore important that individuals consult a physician as soon as symptoms are suspected. This study aimed to investigate the length of time between symptom onset and physician consultation in the UK for occupational asthma including variations by factors such as physician type and causal agents. Methods: Incident cases of occupational asthma reported by chest physicians and occupational physicians (OPs) to The Health and Occupation Research (THOR) network were extracted (2006–2017). For each case, physicians provide the diagnosis, age and sex, occupation, industry, suspected causal agent(s) and (since 2006) the date of symptom onset – either partial (year only) or full (month and year). Time (in months) between symptom onset and first physician consultation was estimated (using both partial and full data) and analysed by physician type and causal agents. Results: Of the 1193 cases of asthma reported by chest physicians, 1098 (92%) had either partial (306, 28%) or full (792, 72%) date of symptom onset provided. This compared to 124 (91%) of the 137 asthma cases reported by OPs (partial: 22, 18%; full: 102, 82%). The median length of time between symptom onset and first consultation was 23 months (range: 0–455 months) for chest physicians compared to 8 months (0–192 months) for OPs. 69% of OP cases were seen within 12 months (compared to 36% for chest physicians). Comparison between frequently reported agents suggested a longer period of time between symptom onset and (chest physician) consultation for metal working fluids compared to isocyanates or flour (figure 1). Conclusions: OPs tended to see patients sooner after symptom onset compared to chest physicians. Of concern, more than a quarter of cases seen by chest physicians were seen >48 months after symptom onset suggestive of delays in the referral process. This could have implications for the patient's health, prognosis and ability to remain in work. There was also evidence that for some agents – for example metal working fluids – the delays were even greater.